Platelet Distribution width is an Early Indicator of Acute Coronary Syndrome - Pervin, Silpi; Islam, Md Saiful; Ferdoushi, Sheuly; Hossain, Mosharaf; Sultana, Tuhin; Hoque, Md Harisul; Ahmed, Chowdhury Meshkat; Ahmed, AN Nashimuddin (University Heart Journal, 2014)
Objective: This cross sectional study was conducted in the dept. of clinical pathology in collaboration with dept. of cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Bangladesh Institute of Research & Rehabilitation of Diabetes Endocrine and Metabolic Disorders (BIRDEM) to evaluate the role of platelet distribution width (PDW) in diagnosing acute coronary syndrome (ACS). Patients & Methods: A total of 142 patients were selected for the study. Of them 79 were cases (patients with acute coronary syndrome) and 63 were controls (patients with non cardiac chest pain). The cardiologist established the diagnosis by clinical examination, ECG and biochemical markers especially troponin I. A structured questionnaire was used which addressed all the variables of interest. Blood samples of the selected patients were taken to investigate their platelet distribution width level and to find its association with ACS. The blood samples was taken properly and processed in a Haematology auto analyzer within 2 hours of collection, which again rechecked manually by peripheral blood film. Statistical analyses were done using mean± standard deviation (SD), t-test, Chi-square (x2) with 95% confidence interval. Test of validity done by receiver operative characteristic curves. Result: In the present study, platelet counts were 273.1±50.15 x 109/L in patients with ACS and 290.78±74.86 x 109/L in control subjects. Platelet counts were slightly low in patients with ACS compared to control subjects. There were no statistical significant differences between the groups in unpaired t- tests. MPV was 12.48±1.17 fl and 10.45±0.66 fl in patients with ACS and control subjects. PDW was 16.23±2.56 fl and 11.89±1.42 fl in patients with ACS and control subjects. Both MPV and PDW were statistically significant between the groups (P<0.001) in unpaired t-test. Patients with acute coronary syndrome the sensitivity, specificity, positive predictive value and negative predictive value of platelet counts, MPV and PDW were obtained by ROC curve and compared with control subjects. The best cut off value of platelet count, MPV & PDW were >225 x 109/L, > 10.7 fl and >12.7 fl respectively. The sensitivity, specificity, accuracy, positive and negative predictive value of platelet counts, MPV and PDW were 83%, 28.1%, 42.3%, 37.6%, 64%; 90.6%, 49.4%, 64.8%, 51.6%, 89.8%; and 94.3%,52.8%, 69%,54.9%, 94.1% respectively. In our study, we found that PDW had higher sensitivity and specificity in contrast to MPV. These PDW are used as predictor for early detection of ACS and risk stratification when other cardiac biomarkers are negative. Conclusion: The PDW is an early indicator to diagnose ACS and correlates with the prognosis of ACS. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19430 University Heart Journal Vol. 9, No. 1, January 2013; 3-8